Wittgenstein on internal and external relations : tracing all the connections - Mácha, Jakub (Bloomsbury Academic, 2015)
"Does Wittgenstein's method of analysis rest on the distinction between internal and external relations? Approaching Wittgenstein's writings from a new perspective, Wittgenstein on Internal and External Relations focuses on how Wittgenstein distinguishes between relations that are grounded in the nature of their related terms, internal, and those which belong to them accidentally, external. This original approach reveals the difference to be one of the most fundamental distinctions that Wittgenstein drew in his writings. Working chronologically, it summarizes the philosophical background against which the distinction emerged, addressing Hegel, Bradley, Russell and Moore. Dealing with Wittgenstein's early and later writings, it distils definitions of the notions of internal and external relations and offers its applications, before concluding with the rationale for Wittgenstein's method of analysis. Making a valuable contribution to Wittgenstein scholarship, Wittgenstein on Internal and External Relations presents significant new insights into his relationship with Russell and Moore and shows how internal and external relations inform his entire philosophical approach."--Bloomsbury Publishing